Entre conquistas e disputas: trajetórias e experiências de luta das mulheres das camadas populares na cidade (Uberlândia/MG anos de 1980-1990) - Amâncio, Kerley Cristina Braz (2014)
From the work with resources such Jornal Correio Newspaper‟s, Participação Newspaper‟s and the Popular Documents Collection (CDP) of the Center for Research and Documentation in History of the Federal University of Uberlândia (UFU-CDHIS), we seek to investigate the participation of the popular women in the organization / coordination of movements in relation to the women\'s movement of the city, in the struggle for positions of power and law, social recognition layers. The time frame chosen contemplates the decades of 1980-1990, when the explosion of popular social movements strands; change in civil society with the 1988 Constitution and the institutionalization of these speeches workers, through agencies and government bodies, which deprives us of many knowledge / history. In this sense, we propose to analyze the formation and constitution of the women\'s movement in the city of Uberlândia, as well as disputes engendered by these other women the search for more visibility to their needs in the context of the city, in order to produce a reflection on the relationship folk / city / rights , questioning about the construction of public space for these new characters poor black women, through social relationships established between them and the women\'s movement in Uberlândia. Along the way, the silenced or hidden these subjects by dominant groups speeches have become indispensable for arguing about their daily lives, their practices, their modes of experimentation / experience of social happening, which for us constitute fertile territory for political education of these subjects sayings such as losers , as well as awareness for development of other movements and social transformation. Thus, through the dialogue with the Social History intend to reflect on the relationship of poor black women said the women\'s movement organized city, in the media newspapers, attending to disputes over the construction of memory / history. Howeve, based on the propositions of Edward P. Thompson on the concept of experience, we want to engage in polemics about the daily life of these historical subjects, as well as their forms of resistance and social change happen and hence the story.